A promising tool for surgical lipotransfer: a constant pressure and quantity injection device in facial fat grafting. Issue 1 (31st May 2017) - Song, Mei; Liu, Yi; Liu, Ping; Zhang, Xianying
Abstract: Background: The purpose of this study was to preliminarily assess a constant pressure and quantity fat granule injection device for minimal invasive properties in clinic. Methods: A retrospective controlled study was carried out, from October 2013 to January 2015, on 76 female healthy patients aged between 26 and 53 years at the General Hospital of Lanzhou Military Command, China. To achieve small volume, high thrust, and precision requirements of facial fat grafting, an integrated handheld controller and motor design was adopted, reducing the volume and weight of the fat transplantation injection device. The 76 patients underwent 90 procedures each side of the face; each patient was treated with the aforementioned device on the face's left side, while a conventional hand-push injection device was used on the right side as control. The outcome was assessed on pre- and postoperative images, with 6-24 months follow-up. Results: The current device consistently allowed deposition of fat threads at about 55 μL/cm after cannula withdrawal; the volume of fat injected could be precisely adjusted to 0.04 mL/s. This device had the advantages of small-volume injection and convenient operation. The patients exhibited a good, stable shape and a smooth contour line in both sides. The long term satisfaction was higher for the left side than for the right one. Nodules and unevenness occurred only on the right side. Ecchymosis occurred significantly less frequent on the left side than the right one. Intraoperative pain was significantly lower for the left side than the right one. Conclusions: This device offered superior control compared with the conventional one and constitutes a promising tool for surgeons practicing lipotransfer.